Wetland extent from a topographic index, wetland's impact on land surface fluxes and a model of CH4 exchange - Kraus, Parker Mayo, author; Denning, A. Scott, advisor; von Fischer, Joe, committee member; Heald, Colette L., committee member (Colorado State University. Libraries, 2011)
A method of estimating wetland extent is developed for use in the land surface components of climate/atmospheric models. The approach is developed within the Simple Biosphere Model, SiB, but is intended as a flexible framework applicable to other models. It uses the topographic index, ln(a/tanβ), to calculate wetland area as a function of regional hydrologic characteristics and model water content. The calculation of the index is discussed, alternatives to the formally required depression-less DEM are investigated and an approach utilizing a smoothed DEM is adopted. Modeled water content is used to establish a point of saturation on the histogram of topographic index, which varies as modeled water content varies, providing estimates of the wetland fraction over time. This relationship is parameterized for the WLEF-TV tower in northern Wisconsin, and tested at locations in Florida and Louisiana. The method of parameterization is found to be acceptable, but site specific parameterization is desirable. Applications of the model are developed. Sensible and latent heat fluxes and net ecosystem exchange modeled with SiB2.5 at the WLEF site are reevaluated with SiB3 and compared to observations. The wetland area model is used to scale SiB3 estimates of these fluxes using a saturated, "wetland," version of the model. Scaling improves estimates, but is overshadowed by errors introduced to the model by changes in the method by which water stress is calculated in SiB. A simple model of methanogenesis and methanotrophy employing predictions of wetland area is proposed and incorporated in SiB. The dynamics of this model are explored in relation to the temperature dependence, Q10, of methanogenic respiration and conditions of equilibrium. Inspection of the model suggests a seasonal cycle of methane flux with summertime emission and fall and springtime consumption. Estimates from the model are compared with Modified Bowen Ratio, MBR, estimates of methane flux based on observations at WLEF site. Observed fluxes offer some empirical constraint on methanogenic Q10, but uncertainties in the methane flux preclude assessment of the variability of wetland area. Methane consumption is overrepresented in the predicted seasonal cycle of methane flux due to the simplified representation of methanotrophy in the model, but the essential expected behavior is confirmed. Verification of model parameters beyond the WLEF is necessary, though the feasibility of modeling variable wetland extent using the topographic index is demonstrated. Applications of the calculation for representing sub-grid scale soil moisture variability and saturated zone biogeochemistry appear promising for use in atmosphere-coupled regional or global model runs.
Keywords: land surface models; wetlands; topographic index; methane